2020
DOI: 10.1038/s42003-020-01366-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genome editing in plants using CRISPR type I-D nuclease

Abstract: Genome editing in plants has advanced greatly by applying the clustered regularly interspaced short palindromic repeats (CRISPRs)-Cas system, especially CRISPR-Cas9. However, CRISPR type I—the most abundant CRISPR system in bacteria—has not been exploited for plant genome modification. In type I CRISPR-Cas systems, e.g., type I-E, Cas3 nucleases degrade the target DNA in mammals. Here, we present a type I-D (TiD) CRISPR-Cas genome editing system in plants. TiD lacks the Cas3 nuclease domain; instead, Cas10d is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 29 publications
(39 reference statements)
5
40
0
Order By: Relevance
“…The results indicated that Cas3d protein exhibit weak ATPase activity (Figure 2A ). The results combined together with our previous study ( 37 ) suggest that both Cas10d and Cas3d cooperate for target DNA cleavage in the type I-D system.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The results indicated that Cas3d protein exhibit weak ATPase activity (Figure 2A ). The results combined together with our previous study ( 37 ) suggest that both Cas10d and Cas3d cooperate for target DNA cleavage in the type I-D system.…”
Section: Resultssupporting
confidence: 81%
“…PCC 6803 ( 32 ). We performed E. coli negative screening using a PAM library with the ccdB expression system, and identified that the type I-D from M. aeruginosa recognized only 5′-GTH-3′ (H = A, C or T) PAM in E. coli cells ( 37 ). We then examined whether GTT is active as the PAM in mammalian cells, and also analyzed the activity of GTC and GTA PAMs (Figure 4A , Supplementary Table S6 ; crRNAs listed in Supplementary Tables S2 and S6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the former, our detection method of biolistic delivery in pollen and pollinated pistils would contribute to increasing the efficiency at various reproductive steps. In the latter regard, a number of approaches aimed at enhancing the efficiency of genome editing have been reported, including the modification of Cas9 (Ling et al 2020; Osakabe et al 2020), design of guide RNA (Moon et al 2019), the use of RNPs (Liang et al 2018; Svitashev et al 2016), and the use of small chemical compounds (Yu et al 2015). Various selection methods have also been reported, including those based on antibiotic resistance (Chesnokov and Manteuffel 2000) and herbicide resistance, by targeting endogenous genes (Han and Kim 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative strategy, several Type I CRISPR-Cas3 systems belonging to Class 1 have been exploited to work as "built-in" genome editing tools in their native hosts (Zheng et al 2020;Xu et al 2021), including Type I-A of Sulfolobus islandicus (Li et al 2016), Type I-B of Haloarcula hispanica (Cheng et al 2017) and Clostridium species (Pyne et al 2016;Zhang et al 2018), Type I-C of Pectobacterium aeruginosa (Csorgo et al 2020), Type I-E of Streptococcus thermophilus (Canez et al 2019) and Lactobacillus crispatus (Hidalgo-Cantabrana et al 2019), and Type I-F of Pectobacterium species (Vercoe et al 2013;Xu et al 2019), and Zymomonas mobilis (Zheng et al 2019), where the processive Cas3 nuclease-helicase was used to generate chromosomal injuries. Recent studies have also employed Type I-D and I-E systems for DNA cleavage in plants (Osakabe et al 2020) and human cells (Cameron et al 2019;Dolan et al 2019;Morisaka et al 2019), respectively, and Type I-E and I-F systems for gene expression modulation in human cells (Pickar-Oliver et al 2019;Chen et al 2020), further broadening the applicability of CRISPR-Cas3-based technologies. These accomplishments have paved a new possibility to develop advanced CRISPR-nCas3 toolkits based on endogenous Type I systems.…”
mentioning
confidence: 99%